Occupational Risk Factors for Laryngeal Cancer in Tunisia: A Case Control Study: Occupational Risk facors For Laryngeal cancer - Gaddour, Asma; Brahem, Aicha; Mosbah, Hiba; Sridi, Chaima; Saidane, Maroua; Kacem, Imen; Maoua, Maher; Kalboussi, Houda; El Maalel, Olfa; Chatti, Souheil; Kermani, Wassim; Najib, Mrizek (La Medicina del Lavoro, 2023)
Background: Tobacco use and alcohol consumption are the primary risk factors for laryngeal cancer (LC). In most populations, occupational exposures are likely to play a minor role in laryngeal carcinogenesis. We aimed to investigate the association between occupational exposure and laryngeal cancer. Methods: It is a case-control study that included 140 cases diagnosed between January 2013 and December 2016 and 140 controls matched by sex, age, alcohol consumption, and tobacco consumption. Results: Significantly increased risks were found amongst workers of the building sector (OR=4.621; 95% CI [1.826-11.693]) and the mechanical industry sector (OR=5.074; 95% CI [1.425-18.072]). Significant association of laryngeal cancer with various carcinogens was observed such as asbestos (p=0.009; OR=3.68; 95% CI [1.29-10.46]), paint vapors (p=0.005; OR=3.35; 95% CI [1.37-8.16]), solvents (p=0.001; OR=3.29: 95% CI [1.61-6.68]) and cement dust (p=0.003; OR=3.19: 95% CI [1.43-7.12]). After binary logistic regression, cement dust was independently correlated with LC (p=0.042; OR=3.93; 95% CI [1.04-14.78]. The administration sector was associated with decreased risk (p=0.001; OR=0.07; 95% CI [0.03-0.15]) as well as the health sector (p=0.001; OR=0.098; 95% CI [0.02-0.43]). Conclusions: Our results supported the role of occupational factors in developing LC. Further studies enabling an in-depth analysis of occupational exposures are necessary to provide a clearer definition of the etiological associations between single agents and circumstances of exposure and the genesis of LC.